1980
DOI: 10.1128/aem.39.3.566-571.1980
|View full text |Cite
|
Sign up to set email alerts
|

Gas-liquid chromatography for evaluating polysaccharide degradation by Ruminococcus flavefaciens C94 and Bacteroides succinogenes S85

Abstract: Two predominant rumen cellulolytic bacteria, Ruminococcus flavefaciens C94 and Bacteroides succinogenes S85, were incubated with ground filter paper (Whatman no. 1), cattle manure fiber, wheat straw, Kentucky bluegrass, alfalfa, and corn silage as substrates. Analyses of the initial substrate and the recovered residue after 48 h of static incubation showed that R. flavefaciens C94 was quantitatively more effective than B. succinogenes S85 in degrading total dry matter (32.3% versus 16.1%). However, B. succinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
5
7
0
Order By: Relevance
“…This study has also demonstrated significant complementary interactions in xylan and hemicellulose hydrolysis that occur among the strains of the combinations FDl plus D1, FDI plus GA33, 7 plus D1 and 7 plus Ga33 (Tables 2 and 3), and these findings support the general view about the complementation occurring in the rumen between the cellulolytic Ruminococcus species and the saccharoclastic species (Dehority & Scott 1967;Collings & Yokoyama 1980;Russell 1984;Kopecny & Williams 1988).…”
Section: Complementary Interactions Among Bacterial Speciessupporting
confidence: 78%
See 4 more Smart Citations
“…This study has also demonstrated significant complementary interactions in xylan and hemicellulose hydrolysis that occur among the strains of the combinations FDl plus D1, FDI plus GA33, 7 plus D1 and 7 plus Ga33 (Tables 2 and 3), and these findings support the general view about the complementation occurring in the rumen between the cellulolytic Ruminococcus species and the saccharoclastic species (Dehority & Scott 1967;Collings & Yokoyama 1980;Russell 1984;Kopecny & Williams 1988).…”
Section: Complementary Interactions Among Bacterial Speciessupporting
confidence: 78%
“…In this study F. succinogenes S85 was the dominant bacterial strain determining the hydrolysis of lucerne CW in all pair combinations employing S85 (Table 1). The high ability of pure F. succinogenes to degrade plant CW was also demonstrated in previous studies (Dehority & Scott 1967;Collings & Yokoyama 1980;Osborne & Dehority 1989). This high hydrolytic ability of S85 can be explained by two characteristics of this species :…”
Section: The Role Of Flbrobecter Succlnopenes S85 In Cw Degradatlonsupporting
confidence: 75%
See 3 more Smart Citations